Обробка графічної інформації за допомогою матриці Адамара - Герасін, О. І. (My University, 2011)
Матриці Адамара широко застосовуються в теорії і практиці цифрової обробки сигналів, завадозахищення передачі інформації. У роботі описаний алгоритм стиснення і передачі інформації. Для навчання студентів створена модель «передавач – приймач» засобами Microsoft Excel. The Hadamard matrices are widely used in theory and application of digital signal processing, noise immune communication. The algorithm of compression and passing to information is in-process described. The model «transmitter – receiver» is created by facilities of Microsoft Excel for teaching of students.
Keywords: матриця фдамара; завадозахищення; стиснення інформації; microsoft excel; макрос; microsoft excel; hadamard matrix; compression information; noise immunity; microsoft excel; macros